MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SD KRISTEN BELSO A2 AMBON DENGAN MENGGUNAKAN MODEL PEMBELAJARAN DOUBLE LOOP PROBLEM SOLVING PADA MATERI PENGUKURAN PANJANG DAN BERAT - Yacob, Herlina; Ayal, Carolina Selfisina; Takaria, Johannis (Jurnal Pendidikan Matematika (JUPITEK), 2019)
This study aims to determine whether there is an increase in students' learning outcomes taught using Double Loop Problem Solving (DLPS) on the measurement material. The design of this study was a pre-experimental design with one group pre test post test design. The research sample was sixth grades which amounted to 24 people. The research techniques used were test and non-test techniques. Analysis of student learning outcomes data descriptively obtained from the results of percentages and average students while to determine the increase in student learning outcomes, we used the N-gain test formula. The results showed that using of the Double Loop Problem Solving (DLPS) learning model could improve student learning outcomes in the measurement material. This is supported by a pre-test and post-test analysis that uses normalized N-gain values where 21% of students are in the N-gain category with a High category, 58% of students are in the moderate category and 21% are in the low category